Mengapa Mesin Pencari Suara Gagal Mengenali Bahasa Indonesia? Sebuah Kajian Awal Tentang ASR (Automatic Speech Recognition) Bahasa Indonesia - Totok Suhardiyanto (Masyarakat Linguistik Indonesia Universitas Andalas, 2013)
This paper is about the study of Indonesian Automatic Speech Recognition (ASR) designed by Informational- Technological Computer ( TIK). Specifically, this paper is aimed at describing how this tool operates in recognizing some in-puts in Indonesian language. TIK industry has something to do with Indonesian PWO Â where the use of the smart phones developes massively in Indonesia. This study processes around 10.774 data in Indonesian language in form of sentence, phrase, and word. From this number, less than 20% can be categorized perfect. The others have an error in format and recognition. This is due to some factors bringing about the failure of ASR in recognising the in put in Indonesian language.